2019
DOI: 10.3390/ijerph16234776
|View full text |Cite
|
Sign up to set email alerts
|

Mood Disorders in Levothyroxine-Treated Hypothyroid Women

Abstract: Background: Hypothyroidism has several symptoms (weight gain, arrhythmias, mood changes, etc.). The aims of this study were (1) to assess the prevalence of anxiety and depression in levothyroxine-treated hypothyroid women and in women without hypothyroidism; (2) to identify variables associated with anxiety and depression. Methods: A case-control study was performed with 393 women. Case-group: 153 levothyroxine-treated hypothyroid women. Control-group: 240 women without hypothyroidism. Convenience sampling. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Hypothyroidism is a disease with an insidious course, characterized by very subtle initial symptoms that hinder the diagnosis. It may cause very different disorders: tiredness, impaired cognition, anxiety disorders, depressive symptoms, decreased information processing speed, reduced efficiency of executive functions, poor learning, dry and coarse skin, muscle weakness, sexual dysfunction, constipation, and weight gain [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism is a disease with an insidious course, characterized by very subtle initial symptoms that hinder the diagnosis. It may cause very different disorders: tiredness, impaired cognition, anxiety disorders, depressive symptoms, decreased information processing speed, reduced efficiency of executive functions, poor learning, dry and coarse skin, muscle weakness, sexual dysfunction, constipation, and weight gain [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overt hypothyroidism was also associated with depression, irritability, and anxiety, which all undoubtedly contributed to SD in both men and women. 14 , 26 , 40 , 41 Romero et al 42 reported that the prevalence of anxiety in hypothyroid patients was 63–65%, and a higher incidence of thyroid dysfunction has been found in patients with depressive disorders. Krysiak et al 24 demonstrated that the presence of hypothyroidism was significantly associated with depression in males.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism manifests itself in a variety of ways (obesity, arrhythmias, mood swings etc.). The study's goals were to [1] determine the occurrence of apprehension and misery in hypothyroid women cured with levothyroxine versus women without hypothyroidism, and [2] identify characteristics linked to anxiety and depression. Techniques: With 393 women, a case-control study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…153 hypothyroid ladies cured with levothyroxine were included in above survey. 240 women without hypothyroidism served as the control group [1].…”
Section: Introductionmentioning
confidence: 99%